1992
DOI: 10.1063/1.463737
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental study of dissolution of inhomogeneities formed during spinodal decomposition in polymer mixtures

Abstract: Dissolution (mixing or melting) of inhomogeneities formed during spinodal decomposition in binary polymer mixtures is studied both experimentally and theoretically. The details of the dissolution experiment with time-resolved light scattering on polystyrene! poly(vinylmethylether) are presented. The theoretical approach differs from that of Langer, Bar-on, and Miller in the way the fluctuations are treated in the nonlinear theory, and in the details of the calculations arising from the chain connectivity (poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
3
28
2
Order By: Relevance
“…It requires one to adjust the starting time for the SD process from 0 to ta' Similar idea has been used in the reverse quench case. 42 In Fig. 11(b), we compare measured S(q,ta;T f) with the structure factor constructed in the same way as above but with t replaced by t-7.98 (min) and S(q,ta=O;T f) equated to S(q,O;T f) ' It is clearly seen that the calculated lines can predict S(q,ta;T f) data well and the peak shift in the very early time of SD.…”
Section: Alternative Data Analysis With Cahn-hilliard-cook Theorymentioning
confidence: 99%
“…It requires one to adjust the starting time for the SD process from 0 to ta' Similar idea has been used in the reverse quench case. 42 In Fig. 11(b), we compare measured S(q,ta;T f) with the structure factor constructed in the same way as above but with t replaced by t-7.98 (min) and S(q,ta=O;T f) equated to S(q,O;T f) ' It is clearly seen that the calculated lines can predict S(q,ta;T f) data well and the peak shift in the very early time of SD.…”
Section: Alternative Data Analysis With Cahn-hilliard-cook Theorymentioning
confidence: 99%
“…PVME. 15 Using time-resolved light scattering, they showed that the kinetics of coarsening and This phase separation interpretation also implies that the morphology should change for off-critical dissolution processes are different. This is because growth occurring during the phase-separacompositions.…”
Section: Introductionmentioning
confidence: 98%
“…The coefficient of the gradient term, which originates from the random phase approximation, is given by: [25] kðfÞ ¼ 1 36…”
Section: Model and Methodologymentioning
confidence: 99%
“…As for an incompressible polymeric blend, we take the Flory‐Huggins expression for the free energy of mixing where χ is the Flory‐Huggins interaction parameter which characterizes the strength of interaction between the species A and B and favors phase separation when it is positive. The coefficient of the gradient term, which originates from the random phase approximation, is given by:25 where $\sigma _{\rm A} (\sigma _{\rm B} )$ is the monomer size (Kuhn length) of species A(B), which is assumed to be equal in this paper.…”
Section: Model and Methodologymentioning
confidence: 99%